Legal Protection of Intellectual Property Rights in the Creative Industry: A Case Study on the Music Industry in Indonesia - Purwaningsih, Ghoncang Novia; Vitrianingsih, Yeni; Mardikaningsih, Rahayu; Issalillah , Fayola (Metromedia, 2025)
The creative industry, particularly the music sector, plays a significant role in Indonesia’s economy by generating employment and national revenue. However, challenges persist in protecting intellectual property rights (IPR) within this industry. This study analyzes the legal protection provided for copyright, trademarks, and patents in Indonesia's music industry, highlighting existing challenges such as piracy, unauthorized use of trademarks, and the neglect of music technology innovations. Despite regulations like Law No. 28 of 2014 on Copyright, Law No. 20 of 2016 on Trademarks and Geographical Indications, and Law No. 13 of 2016 on Patents, enforcement remains weak due to digital complexities, limited public awareness, and inadequate regulatory harmonization. This research employs a normative-empirical method to evaluate the effectiveness of these laws and identify gaps in their implementation. The findings emphasize the need for reform, including stricter enforcement mechanisms, public education, and enhanced collaboration among stakeholders to create a sustainable and equitable ecosystem for the music industry in the digital age.